Naskapi materials, Frank G. Speck papers - Beston, Henry; Beston, Elizabeth Coatsworth; Cooper, John M. (John Montgomery), 1881-1949; Gusinde, Martin, 1886-1969; Myers, John L.; Sapir, Edward, 1884-1939; Speck, Frank G. (Frank Gouldsmith), 1881-1950; White, Richard Jr. (1910)
The Innu and Naskapi materials in the Frank Speck Papers are extensive and found to some degree in most sectionsn of the finding aid. The majority of these materials are identified by Speck as "Montagnais-Naskapi," though they include materials relating to Innu peoples from throughout Québec and Labrador, particularly the communities in the area of Lac St-Jean (Mashteuiatsh; usually given as "Lake St. John" by Speck), St-Augustin (usually "St. Augustine" in Speck); and Naskapi communities in northern and central Labrador. The main body of field work manuscript material is found in Subcollection I, Series II, especially items II(3B1a) through II(4B13). In Series III and IV, there are approximately 500-600 photographs and lantern slides from these communities. Series V contains approximately 12 maps pertaining to Speck's research into hunting territories and place names. In Subcollection II, Series I, see correspondence from Beston, Cooper, Gusinde, Myers, Sapir, and especially the voluminous correspondence with Richard White, a trader in Labrador who provided Speck with extensive information on the Naskapi peoples of the region for decades. In Series II, there are numerous works by Speck, including draft versions of "Naskapi, the Savage Hunters of the Labrador Peninsula." Finally, in Series IV, there is a brief silent film consisting of footage taken of various Innu peoples, including Joseph Kurtness, doing various activities, such as skinning and preparing hides, and singing.